1999
DOI: 10.1029/1999ja900014
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of inner plasma sheet and ring current during substorms

Abstract: Abstract. The evolution of the inner plasma sheet and the ring current during substom dipolarizations is simulated. A substorm cycle is treated by stretching and dipolarizing the magnetosphere according to the Tsyganenko 89 model. In order to clarify the relative influences of steady convection and induction electric field on ring current development, the inductive electric field is superposed on two baseline convective states: a nonstorm state using a weak electric field, and a storm-time state using a strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
106
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(115 citation statements)
references
References 40 publications
(29 reference statements)
9
106
0
Order By: Relevance
“…The extended lifetime of the storm-time injections is associated with both quasi-steady transport (enhanced storm-time convection) and with superposed impulsive injections (implying further substorm onsets). This is consistent with earlier numerical experiments by Wolf et al (1997) and Fok et al (1999), which showed that a substorm dipolarization alone is not sufficient to inject ions into the inner magnetosphere; convection must remain strong during and after the dipolarization in order to bring the fresh plasma close to the Earth to enhance the ring current. The relative importance of convection and induction electric fields in forming the ring current is still a matter of some debate.…”
Section: Role Of Substormssupporting
confidence: 79%
“…The extended lifetime of the storm-time injections is associated with both quasi-steady transport (enhanced storm-time convection) and with superposed impulsive injections (implying further substorm onsets). This is consistent with earlier numerical experiments by Wolf et al (1997) and Fok et al (1999), which showed that a substorm dipolarization alone is not sufficient to inject ions into the inner magnetosphere; convection must remain strong during and after the dipolarization in order to bring the fresh plasma close to the Earth to enhance the ring current. The relative importance of convection and induction electric fields in forming the ring current is still a matter of some debate.…”
Section: Role Of Substormssupporting
confidence: 79%
“…Several studies have concluded that concurrent action of global convection and substorm-associated dipolarization and electric field variations inject plasma closer to the Earth than either one would do individually (Fok et al, 1999;Pulkkinen et al, 2000;Ganushkina and Pulkkinen, 2002). Ganushkina et al (2000Ganushkina et al ( , 2001) studied the penetration of the plasma sheet ions into the inner magnetosphere using the Li et al (1998) model, together with stationary electric and magnetic fields for particle tracing.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Other mechanisms that contribute to ring current flux intensification during the main phase of the storm are radial diffusion (e.g., Chen et al 1994;Jordanova and Miyoshi 2005) and substorm-induced electric fields (e.g., Wolf et al 1997;Fok et al 1999). Radial diffusion affects mostly the local time variations of higher energy (>100 keV) particles, which have drift periods shorter than those of the typical storm main phase and thus drift several times around the Earth during the period of enhanced electric field.…”
Section: How Do Ring Current and Other Geomagnetic Processes Affect Rmentioning
confidence: 99%